Prapolski etnonim Glopeani (głos w dyskusji ) - Łuczyński, Michał (Slavia Occidentalis, 2015)
The article is devoted to the analysis and interpretation of the name „Glopeani”, one of the West-Slavic ethnonyms mentioned in the Bavarian Geographer (around 845 AD). Traditionally, they are assumed to be the „Goplans” and believed to have lived around Lake Gopło in the Kujawy region, with their capital in Kruszwica, beween the 7th and 9th centuries AD. According to an author, the latinized name „Glopeani” should be transcribed as „Głobjanie”. According to many authors, the position of „Glopeani” on the list suggest that this tribe might have lived in Pomerania, Great Poland or Masovia. On the basis of the analysis of Old-Polish toponymy, author attempts to localise the Głobjan tribe in the North-West part of Poland.